The Prevalence of Familial Hemiplegic Migraine With Cerebellar Ataxia and Spinocerebellar Ataxia Type 6 in Portugal. Issue 5 (30th October 2013) - Barros, José; Ruano, Luis; Domingos, Joana; Tuna, Assunção; Damásio, Joana; Alonso, Isabel; Silveira, Isabel; Sequeiros, Jorge; Coutinho, Paula
<x xml:space="preserve">Abstract</x> Background CACNA1A gene disorders present a variable familial phenotype of ataxia, migraine with aura, and/or hemiplegic migraine. Prevalence data for these conditions are scarce. Objective The aim of this study is to report a minimal prevalence estimate for familial hemiplegic migraine with cerebellar ataxia and spinocerebellar ataxia type 6 in Portugal. Methods This is a multisource population‐based prevalence study. Patients and families with spinocerebellar ataxia type 6 and familial hemiplegic migraine and cerebellar ataxia identified through the Portuguese survey of hereditary ataxias and spastic paraplegias were re‐evaluated. Prevalent patients were confirmed to be alive and affected at the 1st of January 2013. Results One family with spinocerebellar ataxia type 6 and 2 families with other CACNA1A gene mutations were identified. From these families, 23 patients were alive and living in Portugal in the prevalence day, for an estimated national prevalence per 100, 000 inhabitants of 0.21 for familial hemiplegic migraine with cerebellar ataxia and of 0.01 for spinocerebellar ataxia type 6. Conclusion The prevalence of familial hemiplegic migraine with cerebellar ataxia and spinocerebellar ataxia type 6 are both probably low in Portugal.